Understanding hydrological connectivity: an empirical study of river-aquifer interaction across Brazil - Uchôa, José Gescilam Sousa Mota (2024)
River-aquifer interactions play a crucial role in advancing our understanding of hydrological processes, influencing terrestrial energy flows, and impacting climatic dynamics. Despite their significance, these interactions are often overlooked in most terrestrial surface and water balance models. Current knowledge primarily stems from localized investigations, with limited empirical studies to a regional scale. Here, a first attempt to characterize long-term riveraquifer conditions in the southern hemisphere is presented, using continental-scale groundwater data that spans the entire Brazilian territory. Through the hydraulic head difference between the river and the underlying aquifer, over 10 thousand losing and gaining rivers were identified. The results indicate that potentially more than half of the analyzed Brazilian rivers drain water into underlying aquifers. Analyzing a set of potential explanatory variables for this river-aquifer interaction phenomenon, the results suggest that climate, geological structure, and groundwater consumption are the main factors contributing to the widespread risk of rivers losing flow to adjacent aquifers rather than gaining from them. Finally, given the difficulty in obtaining public groundwater data, it is suggested that typical terrestrial hydrological and remote sensing observations can be used as a water resource management tool to assess interactions between surface and groundwater in the absence of observed groundwater data. The findings underscore the urgency of coordinated groundwater and surface water policies, providing a foundation for further regional studies. A series of sensitivity analyses indicate that the results of this study are robust. Further research conducted at regional and local scales is needed to translate the insights gained from these long-term measures into practical water management practices at the local level.